Influence of Smoking and Alcohol during Pregnancy on Outcome of VLBW Infants - Spiegler, J.; Jensen, R.; Segerer, H.; Ehlers, S.; Kühn, T.; Jenke, A.; Gebauer, C.; Möller, J.; Orlikowsky, T.; Heitmann, F.; Boeckenholt, K.; Herting, E.; Göpel, W. (Zeitschrift für Geburtshilfe und Neonatologie, 2013)
Nicotine and alcohol consumption have been associated with premature delivery and adverse neonatal outcome. We wanted to analyze the influence of self-reported nicotine and alcohol consumption on outcome of VLBW infants.In an ongoing multicenter study 2 475 parents of former very low birth weight (VLBW) infants born between January 2009 and December 2011 answered questionnaires about maternal smoking habits and alcohol consumption during pregnancy. 2 463 (99.5%) completed questions on alcohol consumption and 2 462 (99.5%) on smoking habits. These infants were stratified to reported maternal smoking and alcohol consumption during pregnancy. We compared the reasons for premature delivery, neonatal outcome and parental reports on bronchitis during the first year of life, as well as growth and development at age 2 years to pregnancy exposure.In nicotine exposed infants intrauterine growth restriction (31 vs. 21%, p<0.01), a birth weight below the 10th percentile (26 vs. 17%, p<0.01) and placenta abruption (9.2 vs. 5.8%, p<0.05) was seen more often. Premature rupture of membranes (24 vs. 30%, p<0.05) or HELLP syndrome (6 vs. 11%, p<0.01) was less frequent. A birth weight below the 3rd percentile was seen more frequently in mothers with reported alcohol consumption (13 vs. 6%, p<0.05). We noted an increased rate of BPD and ROP if mothers reported smoking during pregnancy (p<0.05). Growth parameters and scores on Bayley Sscales of infant development at age 2 years did not differ.Smoking during pregnancy results in a high rate of growth restricted VLBW infants. Prenatal exposition to nicotine seems to increase postnatal complications such as BPD und ROP.
Keywords: very low birth weight infants; outcome; smoking; alcohol